Dissecting the Ethics Court in Indonesia: Problems and Future Regulations from a Legal Philosophy Perspective - Nheo Adi Kurniawan; Deva Mahendra Caesar Bimantya; Zerry Akbar Yudisetyo (Universitas Negeri Surabaya, 2025)
The term